Global Burden of Human Mycetoma: A Systematic Review and Meta-analysis - van de Sande, Wendy W. J. (PLOS Neglected Tropical Diseases, 2013)
Author Summary Mycetoma is a chronic infection resulting in large masses of the subcutaneous tissue of mainly the foot. It can be caused by bacteria or fungi. Treatment for most mycetoma cases is poor and amputations are common. Although this disease was already described almost 200 years ago, it is currently not known how many people over the globe actually suffer from this disease and which countries are mostly affected. These data are useful because they can be used to concentrate medical help in places where it is really needed and to focus to search on new medication on the most common causative agents. Since mycetoma is not a reportable disease, a meta-analysis was performed based from reports in literature, in order to estimate what the global burden of mycetoma is. In total 8763 mycetoma cases were analysed. It appeared that most cases were reported from Mexico, Sudan and India and that the fungus Madurella mycetomatis was the most prevalent causative agent world-wide. Although this study represents a first indication of the global burden on mycetoma, the actual burden is probably much higher. By erecting (inter)national surveillance programs a more accurate estimation of the global burden on mycetoma can be obtained.